2023
DOI: 10.1111/cns.14092
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural alterations of dorsal attention network in preclinical and early‐stage Alzheimer's disease

Abstract: Objectives Subjective cognitive decline (SCD) and amnestic mild cognitive impairment (aMCI) are known as the preclinical and early stage of Alzheimer's disease (AD). The dorsal attention network (DAN) is mainly responsible for the “top‐down” attention process. However, previous studies mainly focused on single functional modality and limited structure. This study aimed to investigate the multimodal alterations of DAN in SCD and aMCI to assess their diagnostic value in preclinical and early‐stage A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
3
6
0
Order By: Relevance
“…We found increased hierarchy, indicated by reduced hyperbolic radii, in the DAN, VAN, and FPN subnetworks for participants experiencing SCD. These findings align with existing evidence of dysfunction in these subnetworks observed in SCD [19], [62], [63], and MCI and AD patients [55], [60], [61]. Furthermore, these three subnetworks were correlated with diminished performance on multiple cognitive assessments.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found increased hierarchy, indicated by reduced hyperbolic radii, in the DAN, VAN, and FPN subnetworks for participants experiencing SCD. These findings align with existing evidence of dysfunction in these subnetworks observed in SCD [19], [62], [63], and MCI and AD patients [55], [60], [61]. Furthermore, these three subnetworks were correlated with diminished performance on multiple cognitive assessments.…”
Section: Discussionsupporting
confidence: 88%
“…At prodromal stages, alterations in the DAN have been consistently observed in patients with MCI [19], [60], [61] and SCD [19], [62], [63]. These alterations have been linked to behavioral deficits in top-down attentional control [61].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on resting-state connectivity has also corroborated the alterations within the DMN and limbic networks (Badhwar et al, 2017). Although altered structural patterns in the dorsal attention network have been reported in AD (Qian et al, 2014) and its early stages (Wu et al, 2023), the relationship between these alterations and the cognitive deficits in the disease remains to be further explored. FHAD-related atrophy has also been localized to the precuneus, a core component of the DMN (Kate et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this pattern of DAN dysfunction has been displayed in the MCI group compared with the CN group between DMN structures. Recent studies have indicated that functional alterations in the DAN could be used as a sensitive marker to forecast the progression from MCI to AD (Pini et al ., 2022 ; Wu et al ., 2022 ; Wu et al ., 2023 ). AD-related decrease of DAN functional connectivity was mainly reported when mean mini-mental state exam score was lower than 14 (Brier et al ., 2012 ; Zhao et al ., 2022 ).…”
Section: Mrimentioning
confidence: 99%